Effect of high sodium ion level on the interaction of AmB with a cholesterol-rich phospholipid monolayer - Wang, Juan; Qiang, Jiahao; Li, Jinzi; Wang, Dengwu (Frontiers in Molecular Biosciences, 2024)
Invasive fungal infection is one of the primary reasons for high mortality in immunocompromised people, especially in incritically ill patients, such as ICU patient, advanced cancer patients or severe burn patients. Hypernatremia also can increase mortality in severely ill patients. Amphotericin B is the gold standard for treating infections, but in severe patients, AmB is prone to hematotoxicity when administered intravenously, due to its interaction with cholesterol on red blood cell membranes. This results in limited doses of AmB and affects the treatment of infections. In the red blood cells, the proportion of cholesterol molecules in membrane lipids is as high as 50 mol%. And the sodium ions can influence the interaction between AmB and lipids on the membrane. Therefore, in the complex clinical situation of a severely ill patient with a fungal infection and hypernatremia, the interaction between amphotericin B and the red blood cell membranes is worth studying in depth. In this work, the interaction between AmB and DPPC/cholesterol mixed monolayer in the presence of high sodium ion levels was studied when the proportion of cholesterol was 50%. The results show that the effect of AmB on reducing the monolayer's area at high level of sodium ions is slightly stronger at 30mN/m. The effect of AmB on reducing the elastic modulus of DPPC/Chol monolayer is significantly weakened by high sodium ion level, compared with the level of sodium ions at normal physiological concentration. The higher the sodium ions' concentration, the weaker the intermolecular force of the DPPC/Chol/AmB mixed monolayers. The SEM and AFM observations suggest that at high sodium ion level, AmB significantly reduces the surface roughness of the DPPC/Chol monolayer. AmB may bind to cholesterol molecules, and it make cholesterol be isolated from the monolayer, resulting in a reduced height of cholesterol-rich monolayer and an increasingly dispersed monolayer region. The results are beneficial to understand the mechanism of impact of high sodium ion level on the relationship between AmB and red blood cell membrane rich in cholesterol, and are valuable for understanding the hemolytic toxicity of AmB to red blood cells at high sodium ion level.